Molecular genetics of autosomal dominant retinitis pigmentosa (ADRP): a comprehensive study of 43 Italian families. Issue 7 (1st July 2005) - Ziviello, C; Simonelli, F; Testa, F; Anastasi, M; Marzoli, S B; Falsini, B; Ghiglione, D; Macaluso, C; Manitto, M P; Garrè, C; Ciccodicola, A; Rinaldi, E; et al.
Abstract : Retinitis pigmentosa is the most common form of retinal degeneration and is heterogeneous both clinically and genetically. The autosomal dominant forms (ADRP) can be caused by mutations in 12 different genes. This report describes the first simultaneous mutation analysis of all the known ADRP genes in the same population, represented by 43 Italian families. This analysis allowed the identification of causative mutations in 12 of the families (28% of the total). Seven different mutations were identified, two of which are novel (458delC and 6901C→T (P2301S), in the CRX and PRPF8 genes, respectively). Several novel polymorphisms leading to amino acid changes in the FSCN2, NRL, IMPDH1, and RP1 genes were also identified. Analysis of gene prevalences indicates that the relative involvement of the RHO and the RDS genes in the pathogenesis of ADRP is less in Italy than in US and UK populations. As causative mutations were not found in over 70% of the families analysed, this study suggests the presence of further novel genes or sequence elements involved in the pathogenesis of ADRP.